2018
DOI: 10.20944/preprints201809.0396.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Finding the Planck Length Independent of Newton's Gravitational Constant and the Planck Constant: The Compton Clock Model of Matter

Abstract: In modern physics, it is assumed that the Planck length is a derived constant from Newton's gravitational constant, the Planck constant and the speed of light, $l_p=\sqrt{\frac{G\hbar}{c^3}}$. This was first discovered by Max Planck in 1899. We suggest a way to find the Planck length independent of any knowledge of Newton's gravitational constant or the Planck constant, but still dependent on the speed of light (directly or indirectly).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…where N is the number of Planck masses in the mass. Our point is the the Schwartzschild radius is linked to the Planck length, and the Planck length can be found independent of any knowledge of G and , but based on gravity observations only, as shown by Haug (2018a). Further, SR is not consistent with such a minimum length.…”
Section: Recent Breakthrough In Relation To the Planck Lengthmentioning
confidence: 77%
See 2 more Smart Citations
“…where N is the number of Planck masses in the mass. Our point is the the Schwartzschild radius is linked to the Planck length, and the Planck length can be found independent of any knowledge of G and , but based on gravity observations only, as shown by Haug (2018a). Further, SR is not consistent with such a minimum length.…”
Section: Recent Breakthrough In Relation To the Planck Lengthmentioning
confidence: 77%
“…However, we have recently shown that the Planck length can be found totally independent of both Newton's gravitational constant and the Planck constant. Based on simple gravity observations, we can find the Planck length and given the speed of light, we can complete just about any gravity predictions that may be needed (Haug, 2018a), see also Haug (2017aHaug ( , 2018b. We only need G when we want to find the weight of an object from gravity observations (and even then we can do without G), which is why Cavendish is considered to be the first one to indirectly measure G by weighing the Earth.…”
Section: Recent Breakthrough In Relation To the Planck Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…We think the Schwarzschild radius plays an important role in gravity, but that it is related to some quite different aspects of matter than those assumed by standard theory. The aware that both p l and λ can be measured independent of GR and without any knowledge of big G, see [25] [26]. For any known elementary particle, such as the electron, the reduced Compton wavelength is much larger than the Planck length.…”
Section: No Need To Know G or The Mass Size Or Even The Speed Of Lighmentioning
confidence: 99%
“…However, we have recently shown that the Planck length can be found totally independent of both Newton's gravitational constant and the Planck constant. Based on simple gravity observations, we can find the Planck length and given the speed of light, we can complete just about any gravity predictions that may be needed [26], see also [19,27,28]. We only need G when we want to find the weight of an object from gravity observations (and even then we can do without G), which is why Cavendish is considered to be the first one to indirectly measure G by weighing the Earth.…”
Section: Recent Breakthrough In Relation To the Planck Lengthmentioning
confidence: 99%